Celebrity-Persona and its Effects on Self-Esteem and Life Satisfaction - Mussarat Jabeen Khan; Fatima Shakeel; Maryam Aslam; Najma Bibi; Rafia Abid; Beenish Aziz; Iffat Sardar (NUST Journal of Social Sciences and Humanities, 2023)
The study was conducted to examine Celebrity-Persona and its Effects on Self-Esteem and Life Satisfaction among university students. Convenience sampling technique was used to collect the data. The sample consisted of 416 individuals, who were investing more than 5 hours a day on fictional content like novels, movies, dramas, and professional stars (e.g., singers, athletes, actors); 239 male participants and 177 female participants. Satisfaction with Life Scale (Diener, Emmons, Larsen, & Griffin, 1985), Celebrity-Persona Parasocial Interaction Scale (CPPI) (Bocarnea & Brown, 2007) and Six-Item State Self Esteem Scale (Heartherton & Polivy, 1991) were used to measure life satisfaction and celebrity persona parasocial interaction and self-esteem respectively. Life satisfaction has significant positive correlation with celebrity persona parasocial interaction and self-esteem. Parasocial interaction has positive correlation with self-esteem. Excessive exposure to fiction content is negatively correlated with life satisfaction. Simple linear regression analysis showed excessive exposure to fiction content as a predictor of life satisfaction and self-esteem among university students. Celebrity persona parasocial interaction worked as a significant mediator in the relationship between excessive exposure to fiction content and satisfaction with life among university students. Independent sample t-test showed that male students have higher life satisfaction than female students.